Hepatic Knockdown of Endothelin Type A Receptor (ETAR) Ameliorates Hepatic Insulin Resistance and Hyperglycemia Through Suppressing p66Shc-Mediated Mitochondrial Fragmentation in High-Fat Diet-Fed Mice - Feng L (Dove Medical Press, 2021)
Li Feng,* Songhua Wang,* Feng Chen,* Cheng Zhang, Qiao Wang, Yuting Zhao, Zifeng Zhang School of Life Science, Jiangsu Normal University, Xuzhou, Jiangsu, 221116, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zifeng Zhang 101 Shanghai Road, Xuzhou, Jiangsu Province, 221116, People’s Republic of ChinaTel + 86 516 83403729Email zhangzifengsuper@jsnu.edu.cnBackground: Emerging evidence from animal studies and clinical trials indicates that systemic inhibition of endothelin1 (ET1) signaling by endothelin receptor antagonists improves pathological features of diabetes and its complications. It is indicated that endothelin type A receptor (ETAR) plays a major role in ET1-mediated pathophysiological actions including diabetic pathology. However, the effects as well as the mechanistic targets of hepatic ET1/ETAR signaling inhibition on the pathology of metabolic diseases remain unclear. This study aimed to investigate the beneficial effects as well as the underlying mechanisms of hepatic ETAR knockdown on metabolism abnormalities in high-fat diet (HFD)-fed mice.Methods: Mice were fed a HFD to induce insulin resistance and metabolism abnormalities. L02 cells were treated with ET1 to assess the action of ET1/ETAR signaling in vitro. Liver-selective knockdown of ETAR was achieved by tail vein injection of adeno-associated virus 8 (AAV8). Systemic and peripheral metabolism abnormalities were determined in vivo and in vitro. Mitochondrial fragmentation was observed by transmission electron microscope (TEM) and mitoTracker red staining.Results: Here we provided in vivo and in vitro evidence to demonstrate that liver-selective knockdown of ETAR effectively ameliorated hepatic insulin resistance and hyperglycemia in HFD-fed mice. Mechanistically, hepatic ETAR knockdown alleviated mitochondrial fragmentation and dysfunction via inactivating 66-kDa Src homology 2 domain-containing protein (p66Shc) to recover mitochondrial dynamics, which was mediated by inhibiting protein kinase Cδ (PKCδ), in the livers of HFD-fed mice. Ultimately, hepatic ETAR knockdown attenuated mitochondria-derived oxidative stress and related liver injuries in HFD-fed mice. These ETAR knockdown-mediated actions were confirmed in ET1-treated L02 cells.Conclusion: This study defined an ameliorative role of hepatic ETAR knockdown in HFD-induced metabolism abnormalities by alleviating p66Shc-mediated mitochondrial fragmentation and consequent oxidative stress-related disorders and indicated that hepatic ETAR knockdown may be a promising therapeutic strategy for metabolic diseases.Keywords: endothelin-1, endothelin type A receptor, 66-kDa Src homology 2 domain-containing protein, mitochondrial fragmentation, metabolism abnormality